PERCEIVED JOB INSECURITY: ITS INDIVIDUAL, ORGANISATIONAL AND SOCIETAL EFFECTS - Adekiya, Adewale, A. (European Scientific Journal, ESJ, 2015)
The concept of perceived job insecurity has been shown to be detrimental for various psychological and health-related outcomes including the effective functioning of business organizations. While most researches have examined the detrimental outcome of this workplace phenomenon from the standpoint of the individual employees and its associated organizational outcome, scanty knowledge exist on the multiplying effect of perceived job insecurity on the larger socio-economic environment and the society at large. This paper examines the overall effect of perceived job insecurity taking into consideration, its overall effects on the individual, organization, and the society. Making use of secondary data from the literature and relevant theories, it was discovered that the effect of perceived job insecurity if not properly addressed, goes beyond the enclave of employees health functioning and its associated organizational dysfunction but can also translate into various forms of adverse social and economic consequences for the society and countries at large. In view of this discovery, recommendations were made for organizations, relevant institutions and government bodies to design a framework that encompasses those institutional and organizational policies that can limit the incidence of perceived job insecurity within the workplace.